Clinical evaluation of two types of ceramic inlays and onlays after 6 months Avaliação clínica de inlays e onlays confeccionadas com dois tipos de cerâmica, após 06 meses - Maria Jacinta M. Coelho Santos; Carlos Eduardo Francischone; Gildo Coelho Santos Júnior; Eduardo Bresciani; José Carlos Romanini; Rosângela Saqueto; Maria Fidela de Lima Navarro (University of São Paulo, 2004)
The aim of the present study was to evaluate the clinical performance of two types of ceramics: a slurry-powder ceramic (Duceram Plus, Degussa) - D and a hot-pressed leucite-based glass-ceramic (IPS Empress, Ivoclar Vivadent) - IPS. Eighty-six restorations, 44 IPS and 42 D, were made by one operator. A total of 33 onlays and 53 inlays on twenty-seven premolars and 59 molars were cemented in 35 patients of both sexes, mean age 35 years. All restorations were cemented with the dual-resin cement (Variolink, Ivoclar-Vivadent) under rubber dam and were evaluated at the baseline and after six months, using the modified U.S.P.H.S. criteria for postoperative sensitivity, secondary caries, fracture, color match, marginal discoloration, marginal integrity and surface texture. Additionally radiographs and intraoral photographs were carried out. At baseline 86 restorations were analyzed and all of them received Alfa rating, except for the following that received Bravo rating for postoperative sensitivity - IPS (2.27%); D (7.14%); for color match - IPS (2.27%); D (2.38%) and for surface texture - IPS (2.27%); D (11.90%). After 6 months 100% of the restorations were analyzed and the following received Bravo rating: color match - IPS (4.55%) and D (9.52%); surface texture - IPS (2.27%) and D (11.9%); marginal discoloration - IPS (6.82%) and D (4.76%) and marginal integrity - IPS (4.55%) and D (7.14%). The results were submitted to the Fisher and McNemar Statistical Tests. No significant differences were noticed between the two ceramics. Both ceramics demonstrated satisfactory clinical performance after six months. Este trabalho se propôs a avaliar a performance clínica de dois tipos de cerâmica: IPS Empress, Ivoclar-Vivadent - IPS e Duceram Plus, Degussa - D. Foram realizadas 86 restaurações por apenas um operador, sendo 44 IPS e 42 D. Vinte e sete pré-molares e 59 molares, num total de 33 onlays e 53 inlays, foram cimentadas em 35 pacientes de ambos os sexos, com idade média de 35 anos. A cimentação das restaurações foi realizada com cimento resinoso dual (Variolink, Ivoclar-Vivadent) sob isolamento absoluto e avaliadas no baseline e após 06 meses, mediante o critério U.S.P.H.S. modificado, quanto à sensibilidade pulpar, reincidência de cárie, fratura, reprodução de cor, descoloração marginal, integridade marginal e textura superficial. Adicionalmente foram realizadas radiografias e fotografias. No baseline foi obtida a classificação Bravo nos itens sensibilidade pulpar - IPS (2,27%); D (7,14%); reprodução de cor - IPS (2,27%); D (2,38%) e textura superficial - IPS (2,27%); D (11,90%). Após 06 meses foram analisadas as 86 restaurações, nas quais foi constatada a classificação Bravo para os itens reprodução de cor - IPS (6,82%); D (2,38%); textura superficial - IPS (2,27%); D (9,52%); descoloração marginal - IPS (6,82%); D (4,76%) e integridade de superfície- IPS (4,55%); D (7,14%). Os resultados obtidos foram submetidos ao Teste Estatístico de Fisher e McNemar. Não houve diferença estatisticamente significante entre as cerâmicas. Pode-se concluir que os dois tipos de cerâmica demonstraram uma performance clínica satisfatória após 06 meses.